Ex Vivo Characterization of a Novel Iodine-123-Labelled Aminomethylchroman as a Potential Agonist Ligand for SPECT Imaging of Dopamine D2/3 Receptors. (25th December 2014) - van Wieringen, Jan-Peter; de Bruin, Kora; Janssen, Henk M.; Fransen, P. Michel; Janssen, Anton G. M.; van Doremalen, Peter A.; Michel, Martin C.; Elsinga, Philip H.; Booij, Jan
Abstract : For imaging of dopamine D2/3 receptors, agonist tracers are favoured over antagonists because they are more sensitive to detection of dopamine release and because they may selectively label the high-affinity receptor state. We have developed novel D2/3 receptor selective agonists that can be radiolabelled with [ 123 I], which label is advantageous over most other labels, such as carbon-11, as it has a longer half-life. Particularly, we considered (R) N-[7-hydroxychroman-2-yl]-methyl 4-iodobenzyl amine (compound1 ) as an attractive candidate for development as it shows high binding affinity to D2/3 receptors in vitro, and here we report on the characterization of this first [ 123 I]-labelled D2/3 receptor agonist radiopharmaceutical intended for SPECT imaging. The appropriate tin precursor for [ 123 I]-1 was developed and was successfully radiolabelled with iodine-123 giving a moderate yield (30–35%) and a good purity (>95%) for [ 123 I]-1 . In biodistribution experiments in Wistar rats intravenous injection of [ 123 I]-1 resulted in a fast brain uptake, where the observed binding in the D2/3 receptor-rich striatum was slightly higher than that in the cerebellum 30 min to 4 h p.i. Storage phosphor imaging experiments, however, did not show specific D2/3 receptor binding. In conclusion, despite promising in vitro data for1, neither specific ex vivo binding nor high signal-to-noise ratios were found in rodents for [ 123 I]-1 .